Influences of size reduction, hydration, and thermal-assisted hydration pretreatment to increase the biogas production from Napier grass and Napier silage. (July 2021) - Jomnonkhaow, Umarin; Sittijunda, Sureewan; Reungsang, Alissara
Graphical abstract: Highlights: An increase in surface area by size reduction resulted in an increase in the MY. Hydration pretreatment using hydrogenic effluent increased the biomass porosity. Thermal-assisted hydration using hydrogenic effluent significantly improved the MY. Recycled hydrogenic effluent for pretreatment of biomass showed promising results. Abstract: Pretreatment of lignocellulose materials prior to biogas production is required to minimize biomass recalcitrance and increase biomass digestibility. In this study, the effects of particle size reduction, hydration, and thermal-assisted hydration on Napier grass and silage for methane production were evaluated. Compared to the 4.75-mm particle size Napier grass and silage, 0.425-mm Napier grass and silage showed 72% and 46% increases in methane yield, respectively, whereas hydration pretreatment using hydrogenic effluent increased the methane yields from Napier grass and silage by 23% and 56%, respectively. Superior effects were observed when Napier grass and silage were pretreated with thermal-assisted hydration using hydrogenic effluent for 60 and 15 min, respectively, resulting in methane yields of 385 and 331 mL CH4 /g substrateadded. The results indicate that size reduction accompanied by thermal-assisted hydration using hydrogenic effluent as a hydration medium significantly improved the biodegradability of Napier grass and silage.